Pengaruh Intellectual Capital Terhadap Return On Asset Pada Bank Umum Syariah di Indonesia Periode Q1.2013 - Q4.2014 - Umi Muhanik; Dina Fitrisia Septiarini (Universitas Airlangga, 2017)
ROA) sharia banks Q1.2013 - Q4.2014 period. The method used is quantitative method with jenuh sampling technique. This study uses 11 Islamic banks and the technique used is the panel data regression. The process of calculating this study using Eviews 8.0 program. Independent variables used Intellectual Capital is VACA, VAHU, STVA and dependent variables use Return on Assets (ROA). The data used is secondary data with the collected data quarterly financial report for the period Q1.2013 – Q4.2014.Hypothesis testing is done using simultaneous significance test (F test) and partial significance test (t test). Panel data analysis conducted showed that simultaneous VACA, VAHU, STVA significant effect on ROA while partial VACA no significant effect on ROA, VAHU significant effect on ROA, STVA no significant effect on ROA.